Pelatihan Pengumpulan dan Pengolahan Data Ukur Bagi Siswa-Siswa Sekolah Dasar Swasta Sukma Bangsa Lhokseumawe - Kaifan, Andrian; Gani, Fauzi A.; Munardy, Munardy; Abdullah, Faisal; Miswar, Khairul; Ruhana, Ruhana; Riyadhsyah, Riyadhsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to provide basic training to students of Sukma Bangsa Lhokseumawe Private Elementary School in collecting and processing measurement data using simple and semi-digital tools, namely tape measures, automatic waterpass, and sound level meters. This training is intended to foster students' initial understanding of the concepts of measuring length, elevation, and environmental noise levels, as well as introducing simple statistical methods such as mode, median, and mean. The implementation methods include delivering materials, demonstrating tool usage, hands-on practice, and processing and interpreting measurement data. The results show that students are able to understand the functions of measuring instruments and process data using basic statistical methods. This activity has proven effective in enhancing science literacy and numeracy among elementary school students.